Consumer perceptions on product carbon footprints and carbon labels of beverage merchandise in Hong Kong. (1st January 2020) - Wong, Eugene Yin Cheung; Chan, Fanny Fong Yee; So, Stuart
Abstract: The increase in beverage production and consumption has received significant attention in environmental sustainability especially in terms of carbon emission. However, there has been a lack of research on consumer perceptions towards carbon label of beverage products. This study derived the carbon footprint of beverage products and analysed consumer behaviour towards carbon labels. An end-to-end beverage product carbon footprint was mapped and analysed. A total of 1, 000 consumers were surveyed on their environmental awareness and on their acceptance of and perceptions towards beverage products with carbon labels. This study's theoretical framework was built on the diffusion of innovation theory, and the model was tested with structural equation modelling. Multi-group analysis was also conducted to examine the moderating effect of consumers' demographic characteristics of the sample, including age, gender and income. This facilitates the development of relevant policies and strategies in accelerating the adoption process. The results show that green advocates in the male group have comparatively more significant influences on the acceptance of low carbon emission products than the consumers in the female group, while green advocates at the age of 50 or above tend to accept low carbon emission products more easily. The awareness, attitudes and likelihood of the public in accepting and adopting low-carbon purchasing practice of beverages were examined and corresponding carbon label policies are recommended. The analysis of consumer behaviour and carbon labels may be extended to a longitudinal study and expanded to nearby countries in future research.